The Spondylogenic Peculiarities Of Vertebrobasilar Insufficiency - Nekrasova, Nataliya (Psychiatry, Neurology and Medical Psychology, 2017)
The paper contains the results of spondylogenic peculiarities of vertebrobasilar insufficiency in young patients. The aim of this investigation is to estimate spondylogenic peculiarities of vertebrobasilar insufficiency in young patients depending on the stage of the disease. With this aim 240 patients with instability in cervical segments of vertebral column on the background of spondylogenic vertebro-basilar insufficiency (VBI) undergoing treatment at the Neurology Department of Kharkiv Regional Clinical Hospital aged from 18 to 44 years have been under our investigation. Depending on clinical and hemodynamic data, the following groups were formed: group 1 – 104 patients with angiodystonic stage of VBI, group 2 – 76 patients with angiodystonic-ischemic stage of VBI, group 3 – 60 patients with ischemic stage of VBI. VBI diagnosis was verified in the hospital according to radiographic, tomographic and ultrasound examination. The control group included 25 healthy volunteers matched by age. On the base of received data the evidence of the most common spondylogenic abnormalities on the segments С4–С5, С5–С6 was proved. The most significant spondylogenic changes at the above discussed level were: instability, spondylolistesis, unko-vertebral arthrosis and hernia of intervertebral disk. The obtained data exposed that progression of VBI is accompanied by simultaneous affection of craniovertebral level and С4–С5, С5–С6levels of cervical vertebral column